A Normative Legal Review of Online Lending Policies in Advertising Fraud in Indonesia - Resty Amelia Kurniawati; Roudlotul Aliyah; Chintya Rosita; Tri Lestari; Davis Ovisena Rabbani; Prasetyo Agus Wibowo; Mustofa Mustofa (CV Edujavare Publishing, 2026)
The rapid development of information technology has exponentially driven the growth of online lending (fintech lending) services in Indonesia. Alongside its ease of access, this phenomenon is accompanied by the proliferation of illegal online lenders who employ misleading advertisements on digital platforms as instruments of fraud. This study aims to analyze the legal regulatory framework governing online lending in Indonesia, identify prevailing advertising fraud schemes, and evaluate the effectiveness of legal protection afforded to victims. This research employs a normative legal methodology incorporating a statute approach and a case approach. The findings indicate that the existing regulations comprising Law No. 8/1999 on Consumer Protection, Law No. 11/2008 on Electronic Information and Transactions (ITE), Law No. 27/2022 on Personal Data Protection, Article 378 of the Criminal Code (KUHP), and OJK Regulation No. 10/POJK.05/2022 are normatively sufficient. However, their enforcement continues to face structural barriers, including the anonymity of digital perpetrators, low financial literacy among the public, and jurisdictional limitations across platforms. This study recommends strengthening inter-agency synergy, intensifying the supervision of digital advertising, and enhancing public legal literacy as strategic countermeasures